State Support of Small and Medium Enterprises in Russia: Spatial Issues - Aleshchenko, Vitaliy (Prostranstvennaâ ékonomica, 2015)
The article is prepared by results of the researches executed at the expense of budgetary funds on the Government task of Financial University, 2014. The paper analyses the spatial asymmetry of the development level of small and medium enterprises (SMEs) and its support by the state in Russian regions. Using the integrated assessments of the development level and per capita state support for SMEs the author makes grouping of subjects of the Russian Federation by 5 taxa: «very high development», «high development», «moderate development», «low development» and «very low development». The researcher also composes two-dimensional matrices based on above indicators (SME development and its state support) for conditions of 2012 and the forecast to 2015 (under the current trend). The study shows that the asymmetry of the development level will persist over time; and maintaining the existing policy of state support for SMEs will only increase differences in the development level between the Russian territories. Moreover, the stability of matrix of the spatial asymmetry of SMEs does not presuppose stable positive changes. This suggests that the existing mechanism of state support for SMEs does not regulate the processes of spatial development